2021
DOI: 10.1186/s40729-021-00346-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of Schneiderian membrane perforations during maxillary sinus floor augmentation with lateral approach in relation to subsequent implant survival rates: a systematic review and meta-analysis

Abstract: Background This systematic review aimed to propose a treatment protocol for repairing intraoperative perforation of the Schneiderian membrane during maxillary sinus floor augmentation (MSFA) procedures with lateral window technique. In turn, to assess subsequent implant survival rates placed below repaired membranes compared with intact membranes and therefore determine whether membrane perforation constitutes a risk factor for implant survival. Material and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 66 publications
3
37
0
6
Order By: Relevance
“…In our study, no postoperative complications were observed resulting from the perforated Schneiderian membrane. This was in line with a previous meta‐analysis that refuted the “panic” over membrane perforation (Díaz‐Olivares et al, 2021). A total of 1598 MSFA operations were included, and the perforation group had no statistically significant lower implant survival rate.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, no postoperative complications were observed resulting from the perforated Schneiderian membrane. This was in line with a previous meta‐analysis that refuted the “panic” over membrane perforation (Díaz‐Olivares et al, 2021). A total of 1598 MSFA operations were included, and the perforation group had no statistically significant lower implant survival rate.…”
Section: Discussionsupporting
confidence: 91%
“…Another retrospective study demonstrated that the implant survival rate in the perforation and non-perforation groups were 100% and 95.5%, respectively [ 54 ]. The review of Díaz-Olivares LA et al reported that there was no significant difference in implant survival rate between the perforation group (97.68%) and non-perforation group (98.88%) ( p = 0.229) with appropriate management to perforation [ 55 ]. Perforation might not affect implant survival rate but it could cause postoperative complications [ 46 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study does not supply long-term outcomes either. However, a systematic review with a meta-analysis reported that the collagen membrane is the most used method for protecting sinus mucosa perforations [ 41 ]. The same review also concluded that such perforations do not entail a risk factor for dental implant survival.…”
Section: Discussionmentioning
confidence: 99%